The Influence of Biocementation on the Compressive Strength of Fireless Bricks - Natalia, Natalia; Indriani, Andi Marini; Utomo, Gunaedy (Universitas Negeri Padang, 2024)
Waste sludge from the Water Treatment Plant (IPA) is used as an additive in the manufacture of environmentally friendly bricks to reduce river pollution. In the process of making these bricks, clay is mixed with sewage sludge at 15% of the total weight of clay. In addition, to reduce the impact of air pollution, the bricks were not burned. This research emphasizes the importance of using environmentally friendly alternative materials in brick production. Bacillus Huizhouensis bacteria was applied to strengthen bricks with variations of bacteria concentration of 8%, as well as bacterial culture age variations of 8 hours, 10 hours, and 15 hours. After the bricks were matured for 14 days, the test results showed that bricks using 8% bacterial solution with 10 hours of culture increased by 70.65% to 1.57 MPa, compared to normal bricks of 0.92 MPa. So that bricks with 8% bacteria with a culture age of 10 hours with a period of 14 days have a higher value than normal bricks.